2018
DOI: 10.1016/j.celrep.2017.12.089
|View full text |Cite
|
Sign up to set email alerts
|

AP2σ Mutations Impair Calcium-Sensing Receptor Trafficking and Signaling, and Show an Endosomal Pathway to Spatially Direct G-Protein Selectivity

Abstract: SummarySpatial control of G-protein-coupled receptor (GPCR) signaling, which is used by cells to translate complex information into distinct downstream responses, is achieved by using plasma membrane (PM) and endocytic-derived signaling pathways. The roles of the endomembrane in regulating such pleiotropic signaling via multiple G-protein pathways remain unknown. Here, we investigated the effects of disease-causing mutations of the adaptor protein-2 σ subunit (AP2σ) on signaling by the class C GPCR calcium-sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 46 publications
4
79
0
1
Order By: Relevance
“…In the last decade, the genetic heterogeneity of FHH and ADH has emerged, with mutations in the Gα11 protein, by which CaSR signals, and the adaptor protein-2 sigma subunit (AP2σ), by which CaSR is internalized, revealed as additional contributors to calcaemic disorders. Studies of these mutations have uncovered novel mechanisms by which CaSR is internalised and demonstrated that CaSR can signal by an endosomal pathway (Gorvin et al 2018c). Moreover, some FHH and ADH patients do not have mutations in any of these three genes and discovery of the mutant proteins in these cases is likely to yield further insights into CaSR signalling and trafficking.…”
Section: Future Directionsmentioning
confidence: 99%
“…In the last decade, the genetic heterogeneity of FHH and ADH has emerged, with mutations in the Gα11 protein, by which CaSR signals, and the adaptor protein-2 sigma subunit (AP2σ), by which CaSR is internalized, revealed as additional contributors to calcaemic disorders. Studies of these mutations have uncovered novel mechanisms by which CaSR is internalised and demonstrated that CaSR can signal by an endosomal pathway (Gorvin et al 2018c). Moreover, some FHH and ADH patients do not have mutations in any of these three genes and discovery of the mutant proteins in these cases is likely to yield further insights into CaSR signalling and trafficking.…”
Section: Future Directionsmentioning
confidence: 99%
“…The AP2σ protein is ubiquitously expressed, and clathrin-mediated endocytosis is a critical cellular process; however, FHH is a largely benign condition, and the phenotypes observed in FHH3 patients are largely CASR-specific. Thus, by studying the AP2σ mutations identified in FHH3, which have been described in a single residue (Nesbit et al 2013b, Hannan et al 2015, novel insights into the trafficking and signalling mechanisms of CASR have been elucidated, and indicate an important interplay between these two processes (Gorvin et al 2018b).…”
Section: Journal Of Molecular Endocrinologymentioning
confidence: 99%
“…This function of β-arrestin has been recognised for CASR in some studies, providing seemingly contradictory information to that in studies of functional desensitisation. Thus, treatment of cells with dominant-negative forms of β-arrestin1 or β-arrestin2, or with siRNA targeting β-arrestin1 or β-arrestin2, reduces the pERK and membrane ruffling signals downstream of CASR (Bouschet et al 2005, Thomsen et al 2012, Gorvin et al 2018b. Further studies are required to determine whether the discrepancies within these data sets are due to experimental differences, differences in cell type or if both desensitisation and enhanced signalling occur downstream of CASR, but at different spatial or temporal points.…”
Section: Regulation Of Cell Surface Expression By Functional Desensitmentioning
confidence: 99%
“…(28) DNA sequence analysis Variants were validated in G2 mice by Sanger DNA sequencing, using appropriate gene-specific primers (Sigma, Gillingham, UK), followed by dideoxynucleotide sequencing using the BigDye Terminator v3.1 Cycle Sequencing Kit (Life Technologies, Carlsbad, CA, USA) and an automated detection system (ABI3730 capillary sequencer; Applied Biosystems, Carlsbad, CA, USA). (29) DNA samples from G2 and G3 mice were assessed by restriction endonuclease analysis using HindIII and BsrDI restriction endonucleases, as described. (20) Protein sequence alignment and protein prediction Protein sequences were aligned using ClustalW (30) and the effect of mutations predicted using MutationTaster (http://www.…”
Section: Exome Sequence Analysismentioning
confidence: 99%
“…Apoptosis was assessed in whole-kidney lysates using the Caspase-Glo 3/7 luminescence assay (Promega) measuring levels of activecaspase 3/7, as described. (29) Luminescence was measured using a Turner Biosystems luminometer (Promega, Southampton, UK). Experiments were performed in 10 independent kidney samples each, from RCALC2 mutant mice and WT littermates.…”
Section: Apoptosis Assaymentioning
confidence: 99%